Evaluating quality and price: A comprehensive analysis of maybelline vinyl ink - Apriani, Luh Ketut; Santra, I Ketut; Jaya, I Made Sura Ambara (Yayasan Mitra Persada Nusantara, 2025)
This study evaluates the quality and pricing of Maybelline Vinyl Ink, a widely popular cosmetic product, to provide insights into consumer perceptions and purchasing behaviour. The research focuses on three primary objectives: understanding the criteria that define cosmetic product quality, comparing Maybelline Vinyl Ink’s pricing with competitors, and analysing factors that influence consumer purchasing decisions. A mixed-methods approach was employed for data collection, incorporating a detailed review of user feedback from various platforms, ingredient analysis, and a comparative market study. Qualitative data provided insights into consumer satisfaction and preferences, while quantitative analysis helped assess market trends and pricing dynamics. The findings reveal that consumers often associate higher prices with superior quality, but this perception is not always accurate. Many affordable beauty products, including Maybelline Vinyl Ink, are recognized for delivering comparable, if not better, performance. Maybelline Vinyl Ink is particularly praised for its rich pigmentation, smooth application, and long-lasting formula. However, some users reported concerns about potential dryness or discomfort after extended wear, which could influence repeat purchases among certain segments. The analysis highlights the importance of balancing quality and pricing in maintaining brand reputation and consumer trust. Maybelline has successfully positioned itself as a reliable brand by offering products that cater to a diverse audience, combining quality and affordability. The study also underscores the role of product innovation, ingredient transparency, and effective marketing in shaping consumer behaviour in the competitive beauty industry. In conclusion, Maybelline Vinyl Ink exemplifies a product that strikes a balance between cost and quality, meeting the expectations of a broad consumer base. The findings provide valuable insights for both consumers and industry players, emphasizing the need for continuous product improvement and competitive pricing strategies in the cosmetics market.